Conventional and biodegradable agricultural microplastics: Effects on soil decomposer animals and protists in three climate zones - Saartama, Vili; van Gestel, Cornelis A.M.; Haimi, Jari; Velmala, Sannakajsa; de Jeu, Lotte; Braun, Melanie; Kaseva, Janne; Pitkänen, Juha-Matti; Post, Derk-Jan; Hasselerharm, Paula Redondo; Rico, Andreu; Sutela, Suvi; et al. (Elsevier, 2026)
The effects of microplastics (MPs) in soils have been studied mainly in laboratory experiments, with limited data on soil invertebrates in field. The importance of different natural environmental factors such as climate for responses of soil organism communities to MPs is not yet studied in detail. We tested whether MPs made of conventional low–density polyethylene (PE) and polybutylene adipate terephthalate starch–blend (PBAT) affect soil invertebrates. We studied the effects of these MPs in agricultural fields in three countries (Finland, Germany, and Spain), representing different climatic zones and soils. Community structure of protists and microfauna (through eDNA), abundances of enchytraeids, earthworms, and microarthropods were analysed in soils dosed with two concentrations (0.005 and 0.05% w/w in top 10 cm layer) and followed for two growing seasons. Enchytraeids showed over 50% decline in numbers in PE and PBAT MP–dosed soils in Finland and Spain. Earthworms exposed to PBAT MPs slightly increased in biomass and numbers in Finland and Germany. Mites were mostly unaffected, while the abundance of springtails decreased in Finland when exposed to PBAT MPs. Protist community changed in Germany and Finland when exposed to PE MPs. Nematode diversity declined when exposed to PE MPs in Finland and PBAT MPs in Germany. Our results suggest that MPs from agricultural origin can impact invertebrates that form significant part of the soil decomposer community, and effects of MPs on soil fauna can vary by geographical region. Therefore, environmental risk assessments must account for local natural conditions to avoid over– or underestimation.
Keywords: microplastics; eDNA; field experiment; earthworms; soil pollution